Algies Pelviennes Aigues De La Femme, Au Centre Hospitalier Universitaire De Brazzaville: Orientation Diagnostique. (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: acute pelvic pain; congo-brazzaville